2008
DOI: 10.1348/135532507x228458
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy violation and perceptions of rape victim credibility

Abstract: Purpose. Rape victims have been found to have a heightened risk of secondary victimization in the legal system through biased perceptions of their credibility. In this study, participants observed a video of a rape victim reporting the crime and evaluated her credibility, to establish the influence of victim emotional expressiveness on evaluations of victim credibility. Methods. The nonverbal (eye‐contact, crying) and paralinguistic (tone of voice) behaviour of the rape victim was manipulated such that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 25 publications
2
46
0
2
Order By: Relevance
“…As Hackett et al (2008) found, heuristics function in conjunction with these expectations such that when the expectation is met (e.g., an emotionally expressive victim where a participant has an expectation that rape victims will be emotionally expressive), this is associated with truthfulness and credibility. The issue is that when this expectation is not met, it reduces the credibility of the rape victim and may be wrongfully attributed to the victim lying.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As Hackett et al (2008) found, heuristics function in conjunction with these expectations such that when the expectation is met (e.g., an emotionally expressive victim where a participant has an expectation that rape victims will be emotionally expressive), this is associated with truthfulness and credibility. The issue is that when this expectation is not met, it reduces the credibility of the rape victim and may be wrongfully attributed to the victim lying.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Ask and Landstrom (2010) established that, in relation to the emotional expressiveness of a rape victim, some people have expectations about the emotions a rape victim will display when reporting their rape to the police. For those participants who held these expectations, the emotionally expressive victim was assessed as more credible compared to the non-emotionally expressive victim (see also Hackett, Day, & Mohr, 2008;Klippenstein & Schuller, 2012). These findings are explained via Expectancy Violation Theory (see Burgoon & Hale, 1988;White, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When an expectancy violation is made, attention is drawn away from the content of the situation and toward the individual in violation, and the possible reasons for that violation (Burgoon, 1993). Therefore, the expectancy of an emotional response (i.e., should the person be expressing emotion) may be a more important determinant of truthfulness than emotional displays on their own (e.g., Ask & Landström, 2010;Klippenstine & Schuller, 2012;Hackett, Day, & Mohr, 2008).…”
Section: The Role Of Emotionmentioning
confidence: 99%
“…More specifically, whereas most EVE studies have dealt with the nonverbal expression of emotions and showed that victims who react in an emotional manner (e.g., crying, sobbing) are perceived as more truthful than victims who react in a controlled, calm, numb, or unemotional manner (e.g., Ask & Landströ m, 2010;Baldry & Winkel, 1998;Bollingmo et al, 2008;Hackett, Day, & Mohr, 2008;Winkel & Koppelaar, 1991), we examine credibility penalties to highly emotional, written Victim Impact Statements (VISs) for different crime types. That is, we measured the influence of crime severity on observers' judgments, by holding constant the emotionality of the VIS.…”
mentioning
confidence: 99%